FAKTOR-FAKTOR PENGARUHI PERILAKU KESEHATAN REPRODUKSI REMAJA KABUPATEN BANYUMAS - Agoeng Noegroho Sunarru Samsi Hariadi Paulus Wiryono Priatamtama (Universitas Gadjah Mada, 2015)
This study analyzed the influence of several factors such as the role of facilitator, variation of counselingmethods, media exposure, parent-adolescent communication, perceived vulnerability, seriousness aboutreproductive health and the assessment of reproductive health threat towards preventive behaviors ofadolescent reproductive health in Banyumas. The study used mixed method with quantitative researchas the dominant approach and supported by qualitative research in the unity of research design. Thesample unit is 149 members of Adolescent Counseling Club group (PIK) taken with census techniquesin Banyumas. The results showed that adolescent reproductive health preventive behavior with someindicators: adolescent often checked reproductive health, refused to have sex before marriage, andprevented sexually transmitted diseases (STDs), affected directly and significantly (p <0.05) by the variableassessment (confidence and awareness) on the health threats with the magnitude of the effect of 0.517.Significantly, some variables, the role of facilitator, variation of counseling methods, media exposure, andparent-adolescent communication, are influencing directly and indirectly preventive reproductive healthbehavior variable, because it should pass the assessment of reproductive health threat variable. It meansthat clues of action variables could improve confidence and awareness on reproductive health threat, andthen became the stimulus for the establishment of preventive behavior of adolescent reproductive health.